(untitled) (Journal of the College of Basic Education, 2026)
The current study aims to investigate the extent to which Islamic education teachers apply performance quality standards in teaching Islamic education, from the perspective of the teachers themselves. The significance of this research lies in highlighting the importance of implementing quality standards as a measure that leads to improved educational outcomes. The study population comprised Islamic education teachers in schools affiliated with the General Directorate of Education in Baghdad, Al-Karkh II, for the academic year 2024–2025. The researcher selected a stratified random sample representing approximately 12% of the total population, consisting of 79 teachers.The descriptive method was adopted as it is considered the most suitable approach for this study. A questionnaire was employed as the research instrument, designed to cover a set of items distributed across six performance standards: professional commitment, classroom management and learning environment organization, mastery of teaching skills, understanding student characteristics, attention to educational activities, and self-assessment of performance.The study revealed several findings, including that Islamic education teachers apply some performance standards at a high level. The highest-rated items were related to professional commitment, such as modesty, dignity, respect, positivity, and fostering respect. However, there was a weakness in applying other performance standards, particularly regarding attention to activities that stimulate creativity and critical thinking, as well as evaluation, utilization of results, diversification of teaching methods, and use of motivation among students. Weaknesses were also observed in time management and role distribution within classroom management. Additionally, no statistically significant differences were found in the application of performance standards based on gender or years of experience.The researcher made several recommendations, including the need to activate assessment strategies as essential tools to ensure teaching quality, and to foster a culture of self-review and exchange of experiences among teachers to enhance awareness of the importance of continuous performance evaluation. It was also suggested to conduct a similar study to explore the obstacles hindering the effective application of performance standards in Islamic education.